Colour management in circular economy: decolourization of cotton waste. (3rd June 2019) - Määttänen, Marjo; Asikainen, Sari; Kamppuri, Taina; Ilen, Elina; Niinimäki, Kirsi; Tanttu, Marjaana; Harlin, Ali
Abstract : Purpose: While aiming to create methods for fibre recycling, the question of colours in waste textiles is also in focus; whether the colour should be kept or should be removed while recycling textile fibre. More knowledge is needed for colour management in a circular economy approach. Design/methodology/approach: The research included the use of different dye types in a cotton dyeing process, the process for decolourizing and the results. Two reactive dyes, two direct dyes and one vat dye were used in the study. Four chemical treatment sequences were used to evaluate colour removal from the dyed cotton fabrics, namely, HCE-A, HCE-P-A, HCE-Z-P-A and HCE-Y-A. Findings: The objective was to evaluate how different chemical refining sequences remove colour from direct, reactive and vat dyed cotton fabrics, and how they influence the specific cellulose properties. Dyeing methods and the used refining sequences influence the degree of colour removal. The highest achieved final brightness of refined cotton materials were between 71 and 91 per cent ISO brightness, depending on the dyeing method used. Research limitations/implications: Only cotton fibre and three different colour types were tested. Practical implications: With cotton waste, it appears to be easier to remove the colour than to retain it, especially if the textile contains polyester residues, which are desired to be removed in the textile refining stage. Originality/value: Colour management in the CE context is an important new track to study in the context of the increasing amount of textile waste used as a raw material.